2009
DOI: 10.1001/archinternmed.2009.336
|View full text |Cite
|
Sign up to set email alerts
|

Percentage of US Emergency Department Patients Seen Within the Recommended Triage Time

Abstract: Background The wait time to see a physician in US emergency departments (EDs) is increasing and may differentially affect patients with varied insurance status and racial/ethnic backgrounds. Methods Using a stratified random sampling of 151 999 visits, representing 539 million ED visits from 1997 to 2006, we examined trends in the percentage of patients seen within the triage target time by triage category (emergent, urgent, semiurgent, and nonurgent), payer type, and race/ethnicity. Results The percentage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 47 publications
2
40
0
Order By: Relevance
“…In the 1990s, crowding first became a concern in inner city and teaching hospital EDs [3,4]. Over the next decade the majority of suburban and rural EDs would also experience crowded conditions [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In the 1990s, crowding first became a concern in inner city and teaching hospital EDs [3,4]. Over the next decade the majority of suburban and rural EDs would also experience crowded conditions [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Several predictors of prolonged WT have been reported such as age of the patient, severity, busyness of the ED, day of the week and time of the day and we confirmed these results in our study. 13,14 However, previous studies have not investigated the influence of the provider on WT, but rather only variables at the patient or the ED level. The association between burnout level of physicians and patient outcomes has rarely been investigated, and evidence of consequences of severe burnout for patients care are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 There are a few previously reported independent predictors of prolonged WT (time of day of the ED visit, age of the patient, overcrowding or daily census for example). [12][13][14][15] However, studies investigating factors associated with a prolonged WT have so far only analyzed factors at the patient level or the ED level, whereas data on the provider (emergency physician) have not been examined.…”
Section: Introductionmentioning
confidence: 99%
“…EDs are the initial points of hospital to where patients refer and they usually suffer from different problems and complications (12). In fact, the final goal of an ED is to provide high quality services in a short time (13)(14)(15). Bernstein et al study on EDWIN scale concluded that the scale could appropriately predict overcrowding in EDs (6).…”
Section: Discussionmentioning
confidence: 99%